Fatty acid ethyl ester synthase inhibition ameliorates ethanol-induced Ca2+-dependent mitochondrial dysfunction and acute pancreatitis. Issue 8 (25th October 2013) - Huang, Wei; Booth, David M; Cane, Matthew C; Chvanov, Michael; Javed, Muhammad A; Elliott, Victoria L; Armstrong, Jane A; Dingsdale, Hayley; Cash, Nicole; Li, Yan; Greenhalf, William; Mukherjee, Rajarshi; et al.
Abstract : Objective: Non-oxidative metabolism of ethanol (NOME) produces fatty acid ethyl esters (FAEEs) via carboxylester lipase (CEL) and other enzyme action implicated in mitochondrial injury and acute pancreatitis (AP). This study investigated the relative importance of oxidative and non-oxidative pathways in mitochondrial dysfunction, pancreatic damage and development of alcoholic AP, and whether deleterious effects of NOME are preventable. Design: Intracellular calcium ([Ca 2+ ]C ), NAD(P)H, mitochondrial membrane potential and activation of apoptotic and necrotic cell death pathways were examined in isolated pancreatic acinar cells in response to ethanol and/or palmitoleic acid (POA) in the presence or absence of 4-methylpyrazole (4-MP) to inhibit oxidative metabolism. A novel in vivo model of alcoholic AP induced by intraperitoneal administration of ethanol and POA was developed to assess the effects of manipulating alcohol metabolism. Results: Inhibition of OME with 4-MP converted predominantly transient [Ca 2+ ]C rises induced by low ethanol/POA combination to sustained elevations, with concurrent mitochondrial depolarisation, fall of NAD(P)H and cellular necrosis in vitro. All effects were prevented by 3-benzyl-6-chloro-2-pyrone (3-BCP), a CEL inhibitor. 3-BCP also significantly inhibited rises of pancreatic FAEE in vivo and ameliorated acute pancreatic damage and inflammation induced by administration of ethanol and POA to mice. Conclusions: A combination of low ethanol and fatty acid that did not exert deleterious effects per se became toxic when oxidative metabolism was inhibited. The in vitro and in vivo damage was markedly inhibited by blockade of CEL, indicating the potential for development of specific therapy for treatment of alcoholic AP via inhibition of FAEE generation.